Willow on Yellowstoneʼs northern range: evidence for a trophic cascade? ... - Merrill, E.; Varley, N.; Boyce, M. S.; Beyer, H. L. (University of Alberta Library, 2007)
Reintroduction of wolves (Canis lupus) to Yellowstone National Park in 1995–1996 has been argued to promote a trophic cascade by altering elk (Cervus elaphus) density, habitat-selection patterns, and behavior that, in turn, could lead to changes within the plant communities used by elk. We sampled two species of willow (Salix boothii and S. geyeriana) on the northern winter range to determine whether (1) there was quantitative evidence of increased willow growth following wolf reintroduction, (2) browsing by elk affected willow growth, and (3) any increase in growth observed was greater than that expected by climatic and hydrological factors alone, thereby indicating a trophic cascade caused by wolves. Using stem sectioning techniques to quantify historical growth patterns we found an approximately twofold increase in stem growth-ring area following wolf reintroduction for both species of willow. This increase could not be explained by climate and hydrological factors alone; the presence of wolves on the ...